Features create a model of radiation contamination man-made tritium - Кряжич, Ольга Олександрівна; Коваленко, Олександр Васильович (Інформаційні технології та комп’ютерна інженерія, 2016)
The approach to the modeling of radioactive contamination of the environment radionuclide hydrogen - tritium. In the simulation takes into account the peculiarities of radionuclides. Simulations made using multiscale models of space-related state system. The adequacy of the model determined by criteria in time and complete information on the results of the monitoring system is studied. The problem of minimizing errors in iterations solved decomposition of functions with residuals. Theoretical calculations confirmed by computer experiment.